Worldwide Research Trends on Wheat and Barley: A Bibliometric Comparative Analysis - Giraldo, Patricia; Benavente, Elena; Manzano-Agugliaro, Francisco; Gimenez, Estela (Agronomy (Basel), 2019)
Grain cereals such as wheat, barley, rice, and maize are the nutritional basis of humans and animals worldwide. Thus, these crop plants are essential in terms of global food security. We conducted a bibliometric assessment of scientific documents and patents related to wheat and barley through the Scopus database. The number of documents published per year, their affiliation and corresponding scientific areas, the publishing journals, document types and languages were metricized. The main keywords included in research publications concerning these crops were also analysed globally and clustered in thematic groups. In the case of keywords related to agronomy or genetics and molecular biology, we considered documents dated up to 1999, and from 2000 to 2018, separately. Comparison of the results obtained for wheat and barley revealed some remarkable different trends, for which the underlying reasons are further discussed.